Neurogênese, astrocitose e perda celular no hipocampo de pacientes com encefalite de Rasmussen - Ferreira, Elane de Nazaré Magno [UNIFESP] (2016)
Rasmussen encephalitis is a serious neurological disease that affects children in early childhood and is considered to have an autoimmune origin. It usually affects only one of the cerebral hemispheres. Their neuropathological features include the presence of microglial nodules and colonization by T lymphocytes in the lesion area. These brain tissue alterations are related to neuronal death and with progressive loss of cognitive and motor functions and other events directly associated to the most affected brain areas. The antiepileptic drug treatment has little influence in seizure control what makes surgical treatment an interesting alternative. The presence of significant inflammatory process, and its relation to the mechanisms underlying epileptogenesis, reveals neurogenesis as an interesting pathophysiological focus that deserves to be investigated, since it is strongly influenced by inflammation and epileptogenesis. Work carried out in recent decades indicates that epileptogenesis, or even the mere occurrence of epileptic seizures, increases hippocampal neurogenesis, whereas inflammation tends to decrease it, since the colonization of brain parenchyma by strains of lymphocytes has been considered to inhibit neurogenesis. Thus, the focus of this thesis addresses the core parameters of relevance to the histopathological study of hippocampal tissue obtained from surgical treatment of Rasmussen's encephalitis patients, ie, the number of neurons and astrocytes, as well as the study of proteins related to neurogenic function. For the control group, it was used brain tissue of people that died for reasons unrelated to neurological diseases. The analysis of hippocampal cellularity revealed no difference between the number of neurons in hippocampal sectors in comparison to the control. Astrocitopenia was observed in hippocampal CA4 region and in the dentate gyrus. The occurrence of pluripotent cells by anti-Sox2 Immunohistochemistry revealed no difference between patients with encephalitis Rasmussen and control cases, while the proliferative rate observed by anti-Ki-67 immunostaining was higher in patients with encephalitis Rasmussen. The intermediate neurofilament (nestin) expression and its co-localization with SSIII-tubulin and BDNF, was more prominent in the hippocampus of patients with Rasmussen Encephalitis. However, these cells showed no co-localization with the other markers. The expression of BDNF was found to be exacerbated in mature hippocampal neurons of patients with Rasmussen's encephalitis, but not in newly generated cells.